The Empowerment of Pragmatic Competence towards Translation Teaching and the Pedagogical Implications in China—A Systematic Review - Zheng, Danyang (Forum for Linguistic Studies, 2024)
Grounded in the rationale of pragmatic competence empowering translation teaching, this study explores the integration of pragmatic competence into translation education, emphasizing its critical role in enhancing translation practices. Through bibliometric analysis using CiteSpace, the research systematically examines the intersection of pragmatic competence and translation studies, revealing a strong theoretical alignment and pedagogical complementarity between the two fields. The bibliometric findings indicate that existing research predominantly focuses on pragmatic processing methods within translation texts, and future research trends are likely to centre on the acquisition of pragmatic translation competence. Based on the bibliometric insights into curriculum implementation and observations of the current state of translation teaching in China, this study advocates for developing a joint pragmatic-translation classroom model. This model emphasizes a process-oriented, constructivist approach to address the current challenges in translation education. It introduces pragmatic real-life contexts and explicit teaching of pragmatic theory and knowledge, supplemented by tools such as Discourse Completion Tests to cultivate pragmatic competence, while focusing on the importance of teacher-student feedback. The proposed model aims to enhance student autonomy, improve cognitive abilities, and promote lifelong learning, ultimately preparing students to navigate the complexities of professional translation tasks. Further empirical research is recommended to refine these pedagogical reforms and assess their long-term impact on translation proficiency.